HARGA SAHAM SEBELUM DAN SESUDAH EX-DIVIDEND DATE PADA PERUSAHAAN JASA DAN MANUFAKTUR DI BURSA EFEK INDONESIA (BEI) (PERIODE 2014 -2015) - Putri, Edwina Liony (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The objective of this research is to find any changes in the stock price of service and manufacturing companies listed in Indonesian Stock Exchange (IDX) before and after ex-dividend date. The population of this research is service and manufacturing companies that consistently pay dividends during 2014-2015. The sample of this study is 76 service companies and 39 manufacturing companies. The observation period of this research is 30 days, which are 15 days before and 15 days after the ex-dividend date. This research uses event study method to observe the movement of stock price in the stock market. To identify any differences in stock price before and after the ex-dividend date, this study uses Wilcoxon signed rank test. The result of this research shows that there are no differences in the stock price of service and manufacturing companies that are listed in the IDX in the period of 2014-2015 before and after the ex-dividend date.Keywords: ex-dividend date, stock price, manufacturing companies, service companies